FARMER GROUP DEVELOPMENT STRATEGY IN SUNGAI RAYA SUB-DISTRICT EAST ACEH REGENCY - Adhiana; Chaidir; Setia Budi; Nove Rina Br Ginting (CV. Radja Publika, 2025)
The study aims to formulate a strategy for developing farmer groups in Sungai Raya District. This study uses a descriptive approach with a SWOT analysis to identify the actual conditions of farmers, while Analytical Business Questions Model (ABQM) was applied to determine priority strategies based on the urgency of the problem and institutional potential. Data were obtained through observation, interviews, and documentation of farmer group in 13 villages. The results showed that Sungai Raya District has significant agricultural potential, supported by land availability, commodity diversity, and support from agricultural extension workers. However, several weakness exist, such as limited capacity, utilizing agricultural technology, increasing access to capital, and developing innovations based on the experience of farmer group members are key factors in supporting the sustainability of farmer groups.